close

標題:

F.4 A.Maths 題

發問:

Find the constant term in the expansion of (1 - 2x)^9 (1+1/x)^3 . 有人識計嗎=.=?? 問左3次= = 有人可以幫幫我嗎?

最佳解答:

Find the constant term in the expansion of (1 - 2x)^9 (1+1/x)^3 Sol: (1 - 2x)^9 (1+1/x)^3 .....={1 - 9(2x) + [9(9-1)(2x)^2] / 2 - [9(9-1)(9-2)(2x)^3]/[(3)(2)] + ........ } [ 1 + 3(1/x) + 3(1/x)^2 + (1/x)^3 ] .....=(1 - 18x + 144x^2 - 672x^3 + ......)(1 + 3/x + 3/x^2 + 1/x^3) The constant term = 1(1) - 18(3) + 144(3) - 672(1) ...........................= 1 - 54 + 432 - 672 ...........................= -293 ( The answer)

其他解答:

常數項等於 (1-2x)9 的常數項乘(1+1/x)3 常數項 (1-2x)9 的x項乘(1+1/x)3 (1/x)項 (1-2x)9 的x2項乘(1+1/x)3 (1/x)2項 (1-2x)9 的x3項乘(1+1/x)3 (1/x)3項 (1 + 1/x)3 = (1 + 3/x + 3/x2 + 1/x3) (1-2x)9 中的常數項為 1 (1-2x)9 中的x項係數為 -9*2 = -18 (1-2x)9 中的x2項係數為 9*8*22/2 = 144 (1-2x)9 中的x3項係數為 -9*8*7*23/3*2 = -672 所以常數項為 1*1 + (3)(-18) + 3(144) + 1(-672) = -293

 

此文章來自奇摩知識+如有不便請留言告知

13413D6BADCE0D57

arrow
arrow
    創作者介紹
    創作者 elahism 的頭像
    elahism

    elahism的部落格

    elahism 發表在 痞客邦 留言(0) 人氣()